Oil price shocks and energy stock returns of ASEAN-5 countries: evidence from Ready’s (2018) decomposition technique in a markov regime switching framework - Adilah Azhari,; Mukhriz Izraf Azman Aziz,; Yong, Kang Cheah; Hazrul Shahiri, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The present study applies a new decomposition technique by Ready (2018) to estimate the impact of oil price shocks on stock return in a Markov Regime Switching framework. The approach solves certain shortcomings of the novel procedure from Kilian by incorporating daily forward-looking prices of traded financial asset. The regime switching regression provides the evidence of strong nonlinear association of stock returns to risk shocks and demand shocks despite the absence of strong regime effects. We also demonstrate that positive demand shocks increase stock returns, whereas positive risk shocks negatively impact stock returns. For supply shocks, findings show that oil supply shocks do not significantly impact stock returns for Malaysia and Singapore. For Indonesia, supply shocks have a significant positive effect only in high volatility state. In the case of Thailand and the Philippines, the effects of supply shocks are negative and significant in high volatility state; but are not significant in low volatility state. Overall, our results suggest that demand shock has a greater economic impact than supply and risk shocks as demonstrated previously by Kilian and Park and Ready.